Alterations of type II classical cadherin, cadherin‐10 (CDH10), is associated with pancreatic ductal adenocarcinomas. Issue 5 (7th March 2017) - Jinawath, Natini; Shiao, Meng‐Shin; Norris, Alexis; Murphy, Kathleen; Klein, Alison P.; Yonescu, Raluca; Iacobuzio‐Donahue, Christine; Meeker, Alan; Jinawath, Artit; Yeo, Charles J.; Eshleman, James R.; Hruban, Ralph H.; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC), either sporadic or familial, has a dismal prognosis and finding candidate genes involved in development of the cancer is crucial for the patient care. First, we identified two patients with germline alterations in or adjacent to CDH10 by chromosome studies and sequencing analyses in 41 familial pancreatic cancer (FPC) cases. One patient had a balanced translocation between chromosome 5 and 20. The breakpoint on chromosome band 5p14.2 was ∼810 Kb upstream of CDH10, while that on chromosome arm 20p was in the pericentromeric region which might result in inactivation of one copy of the gene leading to reduced expression of CDH10 . This interpretation was supported by loss of heterozygosity (LOH) seen in this region as determined by short tandem repeat analyses. Another patient had a single nucleotide variant in exon 12 (p.Arg688Gln) of CDH10 . This amino acid was conserved among vertebrates and the mutation was predicted to have a pathogenic effect on the protein by several prediction algorithms. Next, we analyzed LOH status in the CDH10 region in sporadic PDAC and at least 24% of tumors had evidence of LOH. Immunohistochemical stains with CDH10 antibody showed a different staining pattern between normal pancreatic ducts and PDAC. Taken together, our data supports the notion that CDH10 is involved in sporadic pancreatic carcinogenesis, and might have a role in rare cases of FPC. Further functional studies are needed to elucidate the tumor suppressive role of CDH10 in pancreatic carcinogenesis.